A method for microwave-assisted preparation of heteroatom-doped activated carbon fiber composite material

CN123017754APending Publication Date: 2026-10-30KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611411268.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]为解决传统水热法制备金属氧化物/碳材料复合材料存在的反应时间较长、升温速度相对较慢、所制得材料性能较差等问题,本发明提供了一种微波辅助制备杂原子掺杂活性碳纤维复合材料的方法

Benefits of technology

本发明采用微波辅助水热的方法可在碱性条件下促进Sb2O3形成并负载于S、N共掺杂活性碳纤维表面。与常规水热方法相比,微波辅助加热可为Sb2O3的成核与生长提供更适宜条件。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017754A_ABST
    Figure CN123017754A_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing a heteroatom-doped active carbon fiber composite material by microwave assistance and belongs to the technical field of electrochemical energy storage materials. The method provides more suitable conditions for the nucleation and growth of Sb2O3 by introducing a microwave-assisted hydrothermal method, and the preparation efficiency of the heteroatom-doped active carbon fiber composite material can be improved by combining the pre-constructed S and N co-doped active carbon fiber, and the local agglomeration of active substances is reduced. In addition, under the microwave assistance, the loading of Sb2O3 is more favorable to improve the electron transmission capacity of the composite material and reduce the ion diffusion resistance, and an electrode material more suitable for supercapacitors is obtained. The preparation method provided by the application is simple in process and short in reaction time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical energy storage materials technology, specifically relating to a method for microwave-assisted preparation of heteroatom-doped active carbon fiber composite materials. Background Technology

[0002] With the development of portable electronic devices, new energy systems, and energy storage devices, higher requirements are being placed on electrochemical energy storage devices with fast charging and discharging, high power output, and long cycle life. Supercapacitors are characterized by fast charging and discharging speeds, high power density, and long cycle life, and the composition, structure, and interface characteristics of their electrode materials have a significant impact on their electrochemical energy storage performance.

[0003] Carbon-based materials possess excellent electrical conductivity, high structural stability, and a large specific surface area, making them widely used in supercapacitor electrode materials. However, traditional carbon materials primarily rely on electrical double-layer capacitance for energy storage, and their energy storage capacity is limited by the number of surface active sites. Metal oxides have abundant redox active sites, which can contribute to pseudocapacitance, but some metal oxides suffer from insufficient conductivity, active material aggregation, and structural changes during cycling. Therefore, combining carbon materials with metal oxides is an effective way to improve the electrochemical performance of electrode materials.

[0004] Antimony trioxide (Sb₂O₃) possesses certain redox activities and tunable structural characteristics, making it suitable as an active component for electrochemical energy storage. However, when used alone as an electrode material, Sb₂O₃ is prone to problems such as active particle aggregation and insufficient contact between the active material and the conductive network, thus affecting electron transport and the effective utilization of electrolyte ions. Activated carbon fibers, with their continuous carbon skeleton and large surface area, can provide conductive support and loading space for metal oxides. Modifying activated carbon fibers with heteroatoms such as S and N can alter the chemical environment of the carbon material surface and introduce certain defects and active sites, which is beneficial for improving the interfacial contact between carbon fibers and inorganic active materials.

[0005] Currently, metal oxide / carbon composite materials are typically prepared using hydrothermal and solvothermal methods. However, traditional hydrothermal methods suffer from problems such as long reaction times, relatively slow heating rates, and poor material properties. Summary of the Invention

[0006] To address the problems of long reaction times, relatively slow heating rates, and poor material properties in traditional hydrothermal methods for preparing metal oxide / carbon composite materials, this invention provides a microwave-assisted method for preparing heteroatom-doped activated carbon fiber composite materials. The microwave-assisted hydrothermal method introduced in this invention provides more suitable conditions for the nucleation and growth of Sb₂O₃. Combined with pre-constructed S and N co-doped activated carbon fibers, it can improve the efficiency of composite material preparation and reduce local agglomeration of active materials. Furthermore, loading Sb₂O₃ under microwave assistance is more conducive to improving the electron transport capability of the composite material and reducing ion diffusion resistance, resulting in electrode materials more suitable for use in supercapacitors.

[0007] To achieve the above objectives, the present invention provides the following technical solution: One of the technical solutions of this invention is to provide a method for microwave-assisted preparation of heteroatom-doped activated carbon fiber composite materials, comprising the following steps: Pretreated activated carbon fiber (ACF) is obtained by acidification pretreatment of carbon fiber (CF). The pretreated activated carbon fibers were impregnated in a thiourea solution, then dried and heat-treated under an inert atmosphere to obtain S,N co-doped activated carbon fibers (S,N-ACF). The S and N co-doped activated carbon fibers were added to a solution containing an antimony source and diethylene glycol, the pH of the system was adjusted to alkaline, and a hydrothermal reaction was carried out under microwave assistance to obtain a heteroatom-doped activated carbon fiber (S,N-ACF / Sb2O3) composite material.

[0008] The acidification pretreatment of this invention improves the wettability of the carbon fiber surface and introduces certain surface active sites, providing a foundation for the subsequent introduction of S and N elements and the loading of antimony species. Further, thiourea impregnation and heat treatment introduce sulfur- and nitrogen-containing structures into the activated carbon fibers and regulate the chemical environment of the carbon fiber surface, providing conditions for the subsequent composite of antimony species with the carbon fibers. The microwave-assisted hydrothermal treatment provides more suitable conditions for the nucleation and growth of Sb₂O₃, thereby improving the efficiency of composite material preparation and reducing local agglomeration of active materials. Furthermore, microwave-assisted loading of Sb₂O₃ is more conducive to improving the electron transport capacity of the composite material and reducing ion diffusion resistance, resulting in a more suitable electrode material for supercapacitors.

[0009] Preferably, the acid used in the acidification pretreatment is a mixed acid of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:2~4, and the pretreatment temperature is 40~80℃ for 1~4h.

[0010] Preferably, the acidification pretreatment further includes washing to neutralization and drying steps.

[0011] Preferably, the concentration of the thiourea solution is 0.1~0.5 mol / L.

[0012] Preferably, the ratio of the carbon fiber to the thiourea solution is 30-60 mg: 50 mL.

[0013] Preferably, the impregnation treatment involves first sonicating for 10-60 minutes, followed by soaking in 6-24g of water.

[0014] Preferably, the heating rate of the heat treatment is 3~10℃ / min, the temperature is 650~800℃, and the holding time is 1~3h.

[0015] Preferably, the ratio of antimony, diethylene glycol, and water in the solution containing antimony source and diethylene glycol is 1~3 mmol: 15~25 mL: 5~15 mL.

[0016] Optionally, the antimony source includes SbCl3.

[0017] Preferably, the ratio of the S and N co-doped activated carbon fibers to the solution containing the antimony source and diethylene glycol is 20~80 mg: 20~40 mL.

[0018] Preferably, the alkaline pH range is 8-10, and a 0.5-2 mol / L NaOH solution is used to adjust it to alkalinity.

[0019] Preferably, the microwave power for the hydrothermal reaction under microwave assistance is 200~800W, the reaction temperature is 160~200℃, and the reaction time is 1~4h.

[0020] The second technical solution of the present invention provides a method for preparing heteroatom-doped active carbon fiber composite materials using microwave-assisted preparation.

[0021] The third technical solution of the present invention provides an application of the above-mentioned heteroatom-doped active carbon fiber composite material in the preparation of supercapacitors.

[0022] The beneficial technical effects of the present invention are as follows: This invention employs a microwave-assisted hydrothermal method to promote the formation and loading of Sb₂O₃ onto the surface of S and N co-doped activated carbon fibers under alkaline conditions. Compared with conventional hydrothermal methods, microwave-assisted heating provides more suitable conditions for the nucleation and growth of Sb₂O₃.

[0023] This invention promotes the nucleation and growth of Sb2O3 on the carbon fiber surface by pre-constructing an S and N co-doped activated carbon fiber skeleton, introducing heteroatoms and surface active sites, and combining it with a microwave-assisted hydrothermal process. This improves the preparation efficiency of the composite material, enhances the contact between the active components and the carbon fiber, and reduces the local agglomeration of the active material.

[0024] In the heteroatom-doped activated carbon fiber composite material prepared by this invention, S and N co-doped activated carbon fibers provide a continuous conductive framework for Sb2O3, while Sb2O3 provides electrochemical active sites. The two form a composite structure, which is beneficial to improving the electron transport capability of the composite material and reducing the ion diffusion resistance, making the composite material more suitable as an electrode material for supercapacitors. Attached Figure Description

[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0026] Figure 1 Cyclic voltammetry curves of the S,N-ACF / Sb2O3 composite material prepared in Example 1 at different scan rates.

[0027] Figure 2 The constant current charge-discharge curves of the S,N-ACF / Sb2O3 composite material prepared in Example 2 under different current densities are shown.

[0028] Figure 3 The S,N-ACF / Sb2O3 composite materials prepared in Example 3 and Comparative Example 1 were subjected to a temperature of 50 mV·s. -1 Cyclic voltammetry curves at scan rate.

[0029] Figure 4 The S,N-ACF / Sb2O3 composite materials prepared in Example 4 and Comparative Example 1 were subjected to a reaction at 1 A·g -1 Constant current charge-discharge curves at current density.

[0030] Figure 5 The chemical impedance spectroscopy (CIS) spectra of the S,N-ACF / Sb2O3 composite materials prepared in Example 4 and Comparative Example 1 are shown. Detailed Implementation

[0031] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.

[0032] It should be noted that any aspects not described in detail in this invention are conventional practices in the field and are not the focus of this invention.

[0033] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, are also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0034] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar to or equivalent to those described herein may be used in the implementation or testing of this invention.

[0035] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0036] Unless otherwise specified, room temperature in this invention refers to a temperature of 20±10℃.

[0037] The concentrated nitric acid (65~68wt%) and concentrated sulfuric acid (95~98wt%) used in this invention are both commercially available concentrations.

[0038] Example 1 Steps for microwave-assisted preparation of S,N-ACF / Sb2O3 composite materials: Step 1: Weigh 40 mg of carbon fiber (CF) and add it to a mixed acid solution prepared by a volume ratio of concentrated nitric acid and concentrated sulfuric acid of 1:3. Treat the solution in a water bath at 60 °C for 2 h. After the reaction is complete, wash the solution repeatedly with deionized water until the filtrate is neutral, and then vacuum dry it at 60 °C for 12 h to obtain pretreated activated carbon fiber (ACF).

[0039] Step 2: Weigh 0.761 g of thiourea and add it to 50 mL of deionized water to prepare a 0.2 mol / L thiourea solution. Add the pretreated activated carbon fibers obtained in Step 1 to the thiourea solution, sonicate for 30 min, and soak at room temperature for 12 h. After soaking, filter under vacuum without washing with water, and dry under vacuum at 60 ℃ for 12 h; then place in a tube furnace, heat to 700 ℃ at 5 ℃ / min under nitrogen protection and hold for 2 h to obtain S,N co-doped activated carbon fibers (S,N-ACF).

[0040] Step 3: Weigh 0.456 g (2 mmol) of SbCl3 and add it to a mixed solution of 20 mL diethylene glycol and 10 mL deionized water. Stir magnetically for 30 min. Adjust the pH of the reaction system to 9 using 1 mol / L NaOH solution, continue stirring for 30 min, then add 40 mg of S and N co-doped activated carbon fibers and sonicate for 1 h.

[0041] Step 4: Transfer the mixture obtained in Step 3 to a 100 mL polytetrafluoroethylene-lined reaction vessel suitable for microwave reaction, and carry out a microwave-assisted hydrothermal reaction at 400 W power and 180 °C for 2 h. After the reaction, allow it to cool naturally to room temperature. The resulting product is washed three times with deionized water and anhydrous ethanol, filtered, and then vacuum dried at 60 °C for 12 h to obtain the microwave-assisted prepared S,N-ACF / Sb2O3 composite material.

[0042] Example 2 Steps for microwave-assisted preparation of S,N-ACF / Sb2O3 composite materials: Step 1: Weigh 50 mg of carbon fiber (CF) and add it to a mixed acid solution prepared by a volume ratio of concentrated nitric acid and concentrated sulfuric acid of 1:3. Treat the solution in a water bath at 70 °C for 2 h. After the reaction is complete, wash the solution repeatedly with deionized water until the filtrate is neutral, and then vacuum dry it at 60 °C for 12 h to obtain pretreated activated carbon fiber (ACF).

[0043] Step 2: Weigh 1.52 g of thiourea and add it to 50 mL of deionized water to prepare a 0.4 mol / L thiourea solution. Add the pretreated activated carbon fibers obtained in Step 1 to the thiourea solution, sonicate for 30 min, and soak at room temperature for 6 h. After soaking, filter under vacuum without washing with water, and dry under vacuum at 60 ℃ for 12 h; then place in a tube furnace, heat to 650 ℃ at 5 ℃ / min under nitrogen protection and hold for 2 h to obtain S,N co-doped activated carbon fibers (S,N-ACF).

[0044] Step 3: Weigh 0.684 g (3 mmol) SbCl3 and add it to a mixed solution of 20 mL diethylene glycol and 10 mL deionized water. Stir magnetically for 60 min. Adjust the pH of the reaction system to 9 using 2 mol / L NaOH solution, continue stirring for 30 min, then add 50 mg of S and N co-doped activated carbon fibers and sonicate for 1 h.

[0045] Step 4: Transfer the mixture obtained in Step 3 to a 100 mL polytetrafluoroethylene-lined reaction vessel suitable for microwave reaction, and carry out a microwave-assisted hydrothermal reaction at 200 W power and 160 °C for 4 h. After the reaction, allow it to cool naturally to room temperature. The resulting product is washed three times with deionized water and anhydrous ethanol, filtered, and then vacuum dried at 60 °C for 12 h to obtain the microwave-assisted prepared S,N-ACF / Sb2O3 composite material.

[0046] Example 3 Steps for microwave-assisted preparation of S,N-ACF / Sb2O3 composite materials: Step 1: Weigh 30 mg of carbon fiber (CF) and add it to a mixed acid solution prepared by a volume ratio of concentrated nitric acid and concentrated sulfuric acid of 1:3. Treat the solution in an 80 °C water bath for 1 h. After the reaction is complete, wash the solution repeatedly with deionized water until the filtrate is neutral, and then dry it under vacuum at 60 °C for 12 h to obtain pretreated activated carbon fiber (ACF).

[0047] Step 2: Weigh 0.381 g of thiourea and add it to 50 mL of deionized water to prepare a 0.1 mol / L thiourea solution. Add the pretreated activated carbon fibers obtained in Step 1 to the thiourea solution, sonicate for 30 min, and soak at room temperature for 24 h. After soaking, filter under vacuum without washing with water, and dry under vacuum at 60 ℃ for 12 h; then place in a tube furnace, heat to 700 ℃ at 5 ℃ / min under nitrogen protection and hold for 2 h to obtain S,N co-doped activated carbon fibers (S,N-ACF).

[0048] Step 3: Weigh 0.228 g (1 mmol) of SbCl3 and add it to a mixed solution of 15 mL diethylene glycol and 15 mL deionized water. Stir magnetically for 60 min. Adjust the pH of the reaction system to 8 using 0.5 mol / L NaOH solution, continue stirring for 30 min, then add 30 mg of S and N co-doped activated carbon fibers and sonicate for 1 h.

[0049] Step 4: Transfer the mixture obtained in Step 3 to a 100 mL polytetrafluoroethylene-lined reaction vessel suitable for microwave reaction, and carry out a microwave-assisted hydrothermal reaction at 300 W power and 160 °C for 2 h. After the reaction, allow it to cool naturally to room temperature. Wash the obtained product three times with deionized water and anhydrous ethanol, filter it, and then vacuum dry it at 60 °C for 12 h to obtain the microwave-assisted prepared S,N-ACF / Sb2O3 composite material.

[0050] Example 4 Steps for microwave-assisted preparation of S,N-ACF / Sb2O3 composite materials: Step 1: Weigh 60 mg of carbon fiber (CF) and add it to a mixed acid solution prepared by a volume ratio of concentrated nitric acid and concentrated sulfuric acid of 1:3. Treat the solution in a water bath at 60 °C for 2 h. After the reaction is complete, wash the solution repeatedly with deionized water until the filtrate is neutral, and then vacuum dry it at 60 °C for 12 h to obtain pretreated activated carbon fiber (ACF).

[0051] Step 2: Weigh 0.761 g of thiourea and add it to 50 mL of deionized water to prepare a 0.2 mol / L thiourea solution. Add the pretreated activated carbon fibers obtained in Step 1 to the thiourea solution, sonicate for 30 min, and soak at room temperature for 12 h. After soaking, filter under vacuum without washing with water, and dry under vacuum at 60 ℃ for 12 h; then place in a tube furnace, heat to 800 ℃ at 3 ℃ / min under nitrogen protection and hold for 1 h to obtain S,N co-doped activated carbon fibers (S,N-ACF).

[0052] Step 3: Weigh 0.684 g (3 mmol) of SbCl3 and add it to a mixed solution of 20 mL diethylene glycol and 10 mL deionized water. Stir magnetically for 60 min. Adjust the pH of the reaction system to 10 using 2 mol / L NaOH solution. Continue stirring for 30 min, then add 60 mg of S and N co-doped activated carbon fibers and sonicate for 1.5 h.

[0053] Step 4: Transfer the mixture obtained in Step 3 to a 100 mL polytetrafluoroethylene-lined reaction vessel suitable for microwave reaction, and carry out a microwave-assisted hydrothermal reaction at 600 W power and 180 °C for 4 h. After the reaction, allow it to cool naturally to room temperature. Wash the obtained product three times with deionized water and anhydrous ethanol, filter it, and then vacuum dry it at 60 °C for 12 h to obtain the microwave-assisted prepared S,N-ACF / Sb2O3 composite material.

[0054] Comparative Example 1 The conventional hydrothermal preparation steps for S,N-ACF / Sb2O3 composite materials are as follows: Step 1: Weigh 40 mg of carbon fiber (CF) and add it to a mixed acid solution prepared by a volume ratio of concentrated nitric acid and concentrated sulfuric acid of 1:3. Treat the solution in a water bath at 60 °C for 2 h. After the reaction is complete, wash the solution repeatedly with deionized water until the filtrate is neutral, and then vacuum dry it at 60 °C for 12 h to obtain pretreated activated carbon fiber (ACF).

[0055] Step 2: Weigh 0.761 g of thiourea and add it to 50 mL of deionized water to prepare a 0.2 mol / L thiourea solution. Add the pretreated activated carbon fibers obtained in Step 1 to the thiourea solution, sonicate for 30 min, and soak at room temperature for 12 h. After soaking, filter under vacuum without washing with water, and dry under vacuum at 60 ℃ for 12 h; then place in a tube furnace, heat to 700 ℃ at 5 ℃ / min under nitrogen protection and hold for 2 h to obtain S,N co-doped activated carbon fibers (S,N-ACF).

[0056] Step 3: Weigh 0.456 g (2 mmol) of SbCl3 and add it to a mixed solution of 20 mL diethylene glycol and 10 mL deionized water. Stir magnetically for 30 min. Adjust the pH of the reaction system to 9 using 1 mol / L NaOH solution, continue stirring for 30 min, then add 40 mg of S and N co-doped activated carbon fibers and sonicate for 1 h.

[0057] Step 4: Transfer the mixture obtained in Step 3 to a 100 mL polytetrafluoroethylene-lined reaction vessel suitable for microwave reaction, and carry out a conventional hydrothermal reaction at 180℃ for 2 h. After the reaction, allow it to cool naturally to room temperature. Wash the obtained product three times with deionized water and anhydrous ethanol, filter it, and then vacuum dry it at 60℃ for 12 h to obtain the microwave-assisted prepared S,N-ACF / Sb2O3 composite material.

[0058] Compared with Example 1, the only difference is that the reaction conditions in step 4 are modified to be a conventional hydrothermal reaction at 180°C for 2 hours.

[0059] The cyclic voltammetry (CV) curves of the S,N-ACF / Sb2O3 composite material prepared in Example 1 at different scan rates are shown in the figure. Figure 1 Electrochemical tests were performed using a three-electrode system. The prepared S,N-ACF / Sb₂O₃ composite material was used as the working electrode, a platinum sheet as the auxiliary electrode, a saturated calomel electrode (SCE) as the auxiliary electrode, and 3M KOH as the electrolyte. The test potential window was 0–0.5 V (vs. SCE), and the scan rates were 20, 40, 60, 80, and 100 mV·s. -1 .

[0060] like Figure 1 As shown, the current response gradually increases with increasing scan rate, and the redox peak remains clear, indicating that the composite material has good pseudocapacitive energy storage characteristics and fast electrochemical reaction kinetics.

[0061] The galvanostatic charge-discharge (GCD) curves of the S,N-ACF / Sb2O3 composite material prepared in Example 2 at different current densities are shown in the figure. Figure 2Electrochemical tests were performed using a three-electrode system. The prepared S,N-ACF / Sb₂O₃ composite material was used as the working electrode, a platinum sheet as the auxiliary electrode, a saturated calomel electrode (SCE) as the auxiliary electrode, and 3M KOH as the electrolyte. The tested current densities were 1, 2, 3, 4, and 5 A·g⁻¹. -1 .

[0062] like Figure 2 As shown, 1, 2, 3, 4 and 5 A·g -1 The specific capacitance corresponding to the current is 943.8 F·g. -1 927.5F·g -1 858.0 F·g -1 799.7 F·g -1 and 762.5 F·g -1 The charge-discharge curves all showed good symmetry and obvious charge-discharge plateaus, indicating that the microwave-synthesized composite material has good reversible redox reaction characteristics and rate performance.

[0063] The S,N-ACF / Sb2O3 composite materials prepared in Example 3 and Comparative Example 1 were subjected to a temperature of 50 mV·s. -1 The cyclic voltammetry curves at the scan rate are shown below. Figure 3 Electrochemical testing was performed using a three-electrode system. The prepared S,N-ACF / Sb₂O₃ composite material was used as the working electrode, a platinum sheet as the auxiliary electrode, a saturated calomel electrode (SCE) as the auxiliary electrode, and 3M KOH as the electrolyte. The test potential window was 0–0.5 V (vs. SCE).

[0064] like Figure 3 As shown, the CV integrated area of ​​the microwave sample is significantly larger than that of the conventional hydrothermal sample, and the redox peak response is more obvious, indicating that the composite material prepared by microwave has good pseudocapacitive energy storage characteristics and fast electrochemical reaction kinetics.

[0065] The S,N-ACF / Sb2O3 composite materials prepared in Example 4 and Comparative Example 1 were subjected to a reaction at 1 A·g -1 The constant current charge-discharge curves at current density are shown below. Figure 4 Electrochemical tests were performed using a three-electrode system. The prepared S,N-ACF / Sb2O3 composite material was used as the working electrode, a platinum sheet as the auxiliary electrode, a saturated calomel electrode (SCE) as the auxiliary electrode, and 3M KOH as the electrolyte.

[0066] like Figure 4 As shown, at 1A·g -1 At the specified current density, the discharge time of the microwave sample was significantly longer than that of the conventional hydrothermal sample, with a specific capacitance of 943.8 F·g. -1 and 184.4 F·g-1 This indicates that samples prepared by microwave have a greater electrochemical energy storage effect.

[0067] The chemical impedance spectroscopy (EIS) spectra of the S,N-ACF / Sb₂O₃ composite materials prepared in Example 4 and Comparative Example 1 are shown below. Figure 5 Electrochemical tests were performed using a three-electrode system. The prepared S,N-ACF / Sb2O3 composite material was used as the working electrode, a platinum sheet as the auxiliary electrode, a saturated calomel electrode (SCE) as the auxiliary electrode, and 3M KOH as the electrolyte.

[0068] like Figure 5 As shown, the intercept and semicircular characteristic of the Nyquist curve of the microwave-assisted sample in the high-frequency region are generally smaller than those of the conventional hydrothermal sample, indicating that its equivalent series resistance and charge transfer resistance have a decreasing trend. In the low-frequency region, the impedance curve of the microwave-assisted S,N-ACF / Sb2O3 composite material is closer to the imaginary axis than that of the conventional hydrothermal sample, indicating that the composite material obtained by microwave-assisted preparation has lower ion diffusion resistance, which is beneficial to the transport of electrolyte ions in the composite electrode. Combined with the impedance characteristics in the high-frequency region, it can be concluded that microwave-assisted heating can improve the interfacial charge transport and ion diffusion behavior of the composite material.

[0069] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. A method for microwave-assisted preparation of heteroatom-doped activated carbon fiber composite materials, characterized in that, Includes the following steps: Pretreated activated carbon fibers were obtained by acidification pretreatment of carbon fibers. The pretreated activated carbon fibers were impregnated in a thiourea solution, then dried and heat-treated under an inert atmosphere to obtain S and N co-doped activated carbon fibers. The S and N co-doped activated carbon fibers were added to a solution containing an antimony source and diethylene glycol, the pH of the system was adjusted to alkaline, and a hydrothermal reaction was carried out under microwave assistance to obtain a heteroatom-doped activated carbon fiber composite material.

2. The method for microwave-assisted preparation of heteroatom-doped activated carbon fiber composite materials according to claim 1, characterized in that, The acid used in the acidification pretreatment is a mixed acid of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:2~4. The pretreatment temperature is 40~80℃ and the time is 1~4h.

3. The method for microwave-assisted preparation of heteroatom-doped activated carbon fiber composite materials according to claim 1, characterized in that, The acidification pretreatment also includes washing to neutralization and drying steps.

4. The method for microwave-assisted preparation of heteroatom-doped activated carbon fiber composite materials according to claim 1, characterized in that, The concentration of the thiourea solution is 0.1~0.5mol / L; and / or, the ratio of the carbon fiber to the thiourea solution is 30~60mg:50mL; and / or, the impregnation treatment is to first sonicate for 10~60min, and then soak for 6~24h.

5. The method for microwave-assisted preparation of heteroatom-doped activated carbon fiber composite materials according to claim 1, characterized in that, The heating rate of the heat treatment is 3~10℃ / min, the temperature is 650~800℃, and the holding time is 1~3h.

6. The method for microwave-assisted preparation of heteroatom-doped activated carbon fiber composite materials according to claim 1, characterized in that, The ratio of antimony, diethylene glycol, and water in the solution containing antimony source and diethylene glycol is 1~3 mmol: 15~25 mL: 5~15 mL; and / or, the ratio of the S, N co-doped activated carbon fiber to the solution containing antimony source and diethylene glycol is 20~80 mg: 20~40 mL.

7. The method for microwave-assisted preparation of heteroatom-doped activated carbon fiber composite materials according to claim 1, characterized in that, The alkaline pH range is 8-10, and a 0.5-2 mol / L NaOH solution is used to adjust it to alkalinity.

8. The method for microwave-assisted preparation of heteroatom-doped activated carbon fiber composite materials according to claim 1, characterized in that, The microwave power for the hydrothermal reaction under microwave assistance is 200~800 W, the reaction temperature is 160~200℃, and the reaction time is 1~4h.

9. A heteroatom-doped activated carbon fiber composite material prepared by the microwave-assisted preparation method for heteroatom-doped activated carbon fiber composite materials according to any one of claims 1 to 8.

10. The application of the heteroatom-doped activated carbon fiber composite material of claim 9 in the preparation of supercapacitors.